Zinc solubilizing Bacillus sp (SS9) and Enterobacter sp (SS7) promote mung bean (Vigna radiata L.) growth, nutrient uptake and physiological profiles. (16th December 2022) - Shreya, Desai; Amaresan, Natarajan; Supriya, Naga Rathna
Abstract: Zinc (Zn) is a crucial micronutrient required for optimum plant growth. ZSB are potential alternatives for Zn supplementation and convert applied inorganic Zn to available forms. In this study, ZSB were isolated from the root nodules of wild legumes. From a set of 17 bacteria, the isolates SS9 and SS7 were found to be efficient in tolerating 1 g (w/v) Zn. The isolates were identified as Bacillus sp (SS9, MW642183) and Enterobacter sp (SS7, MW624528) based on morphology and 16S rRNA gene sequencing. The screening of PGP bacterial properties revealed that both isolates possessed production of indole acetic acid (50.9 and 70.8 µgml –1 ), siderophore (40.2 and 28.0%), and solubilization of phosphate and potassium. The pot study experiment in the presence and absence of Zn revealed that the Bacillus sp and Enterobacter sp inoculated plants showed enhanced mung bean plant growth (45.0 to 61.0% increment in shoot length and 26.9 to 30.9% in root length) and biomass compared to the control. The isolates also enhanced photosynthetic pigments such as total chlorophyll (1.5 to 6.0-fold) and carotenoids (0.5 to 3.0-fold) and 1–2-fold increase in Zn, phosphorous (P) and nitrogen (N) uptake compared to Zn-stressed control. The present results indicated that the inoculation of Bacillus sp (SS9) and Enterobacter sp(SS7) reduced the toxicity of Zn and, in turn, enhanced the plant growth and mobilization of Zn, N, and P to the plant parts.